IMPROVING TEACHING AND LEARNING USING STUDENT APPRAISALS: A CASE STUDY OF A TERTIARY INSTITUTE - Lord, Rigieta (IJRDO- Journal of Educational Research, 2017)
Feedback is being used in education to improve teaching and learning. Through feedback, students are able to gauge their performance and teachers are also able to retrieve information to be used to design assessment and make adjustments for improvement. There are various types of feedback that are being discussed in this project, these include descriptive, evaluative, motivational and effective. These forms of feedback have different purposes which can be summarized to make improvement in the teaching and learning process. Feedback is being used in the education system to achieve learning goals and to inform students if they are on the right track or not. There are various ways in which feedback may be done to ensure that it is effective, the following must be considered, timely, clear and specific, user friendly to name a few. This project argues that student appraisal may be used to improve teaching and learning in a tertiary institution. This project also focuses on the use of student feedback to provide feedback to the Teaching and Learning Development Unit to design student activities as well as professional development session solely to bring about quality assurance. Both students and teachers in the tertiary institution have been used as participants of this project.